The Impact of Postoperative Tumor Burden on Patients With Brain Metastases - Aftahy, Amir Kaywan; Barz, Melanie; Lange, Nicole; Baumgart, Lea; Thunstedt, Cem; Eller, Mario Antonio; Wiestler, Benedikt; Bernhardt, Denise; Combs, Stephanie E.; Jost, Philipp J.; Delbridge, Claire; Liesche-Starnecker, Friederike; et al. (Frontiers in Oncology, 2022)
Background: Brain metastases were considered to be well-defined lesions, but recent research points to infiltrating behavior. Impact of postoperative residual tumor burden (RTB) and extent of resection are still not defined enough. Patients and methods: Adult patients with surgery of brain metastases between 04/2007-01/2020 were analyzed. Early postoperative MRI (<72h) was used to segment RTB. Survival analysis were performed and cut-off values for RTB revealed. Separate (subgroup) analyses regarding postoperative radiotherapy, age and histopathological entities were performed. Results: 704 patients were included. Complete cytoreduction was achieved in 487/704 (69.2%) patients, median preoperative tumor burden was 12.4 cm3 (IQR 5.2-25.8 cm3), median RTB 0.14 cm3 (IQR 0.0-2.05 cm3) and median postoperative tumor volume of the targeted BM was 0.0 cm3 (IQR 0.0-0.1 cm3). Median overall survival was 6 months (IQR 2-18). In multivariate analysis preoperative KPSS (HR 0.981982, 95% CI, 0.9761-0.9873, P < .001), age (HR 1.012363; 95% CI, 1.0043-1.0205, P = .0026), preoperative (HR 1.004906; 95% CI, 1.0003-1.0095, P = .00362) and postoperative tumor burden (HR 1.017983; 95% CI; 1.0058-1.0303, P = .0036) were significant. Maximally selected log rank statistics showed a significant cut-off for RTB of 1.78 cm3 (P = .0022) at all, 0.28 cm3 (P = .0047) for targeted metastasis and cut-off for age of 67 years (P < .001). (Stereotactic) Radiotherapy had a significant impact on survival (P < .001). Conclusions: RTB is a strong predictor for survival. Maximal cytoreduction, as confirmed by postoperative MRI, should be achieved whenever possible, regardless of type of postoperative radiotherapy.